Tsetse invasion in Karamoja, Uganda: An Emerging Threat to Socioecological Resilience - Egeru, Anthony (AirFood, 2018)
Over 70% of Uganda is infested by tsetse with negative effects on human and livestock health. From colonial to post-independent Uganda, the Government of Uganda has strived to eradicate the tsetse menace through various interventions but it is still a threat following reemergence in some areas and the expansion of the tsetse belt. The tsetse challenge had been brought under control in Karamoja subregion in the 1960s eradication effort. However, in the recent past, veterinary reports have indicated tsetse reinvasion estimated at 10 percent prevalence. Tsetse reinvasion of the sub-region represents an additional challenge to the already vulnerable pastoral communities interfacing with a range of constraints including extreme weather events such as drought. The reinvasion has considerable influence on the social-ecological resilience of communities. Participatory assessment reports indicate that tsetse has led to livestock deaths and heightened human-wildlife conflicts owing to the perceived spread by elephants and buffalos that emerge from the Kidepo Valley National Park. Further, livestock abortions among donkeys, goats, sheep and cattle have been reported, decreased milk yield and interference on grazing in the prime grazing lands, and migrations across to Kenya. It is also alluded that women’s labour input into crop production has decreased as the tsetse prevalence is high in some of the most fertile lands yet the women often move with young children to the gardens. These effects are a direct affront on the social-ecological resilience of the pastoral communities in the sub-region as they weaken communities’ adaptive capacity. Cognizant of the potential transboundary character of the tsetse reinvasion sources in Karamoja, an urgent, strategic and system wide intervention should be undertaken in the sub-region.